The Relationship between Exam Frequency and Students’ Achievement in Online Learning - Fauzi, Bella Anastasya Virginia; Sunarti; Rahmawati, Yeni (Jurnal Media dan Teknologi Pendidikan, 2024)
The frequency of examinations plays a crucial role in language teaching, serving as a key indicator of students' understanding of the material. This study aims to analyze the relationship between exam frequency and student achievement in English language learning within the context of online education. The research employs a quantitative approach using correlation analysis to investigate this relationship. Data were collected on the frequency of exams taken by students on the digital learning platform OpenLearning (OPL) and their final exam scores. The study involved a sample of first-semester students selected through random sampling to ensure unbiased representation. The findings reveal a significant positive correlation between exam frequency and student achievement, indicating that more frequent exams are associated with higher final exam scores. Additionally, an Analysis of Variance (ANOVA) confirms significant differences in student achievement based on exam frequency, with students experiencing higher exam frequencies performing better. These results suggest that frequent examinations can enhance learning outcomes by promoting consistent study habits, reducing exam anxiety, and providing regular feedback. The study's implications highlight the importance of integrating regular and frequent assessments in educational strategies to improve academic performance. Future research should explore the optimal frequency of exams and consider other variables such as exam difficulty and student engagement to develop comprehensive approaches for enhancing English language learning in online education environments.